A PROFİLİNG AND SCORECARD DEVELOPMENT EXERCİSE FOR ANALYZİNG AND ASSESSİNG WOMEN’S ENTREPRENEURSHİP İN TURKEY (Third Sector Social Economic Review, 2022)
In recent years, women’s entrepreneurship has become one of the central points within national and international development policies. As it exists in everything, women entrepreneurs face certain gender specific problems with regards to entrepreneurship. Hence, it is important to develop particular support systems and programmes for women entrepreneurs. Following these trends, Turkey is one of such countries supporting women’s entrepreneurship through certain institutions. One of such institutions is İŞKUR. It employs several joint programmes with national and international organizations targeting women entrepreneurs. However, it is equally important to evaluate these programmes and support services in order to identify and address the problems in front of successful establishment and continuation of women’s enterprises. Keeping this in mind, this research paper presents its findings from an İŞKUR programme targeting 400 women in 4 provinces across Turkey between 2017 and 2018. Through the interviews done over the phone with the beneficiaries of this programme, this paper lists recommendations for improving support services. Moreover, in order to enhance monitoring and follow up processes and ensure the tailoring of services in accordance with the needs of women entrepreneurs, it engages in a scorecard developing exercise. In order to do so, it first explains women’s entrepreneurship, develops participant women entrepreneurs’ profiles and identifies problems faced by them. Later, it proposes a set of recommendations for the improvement of programmes. Lastly, it develops a work flow and scorecard sample to guide monitoring and follow up processes.
Keywords: Women’s Entrepreneurship; Profiling; Scorecard Development; Monitoring; İŞKUR.